PENGARUH SISTEM PEMUNGUTAN PAJAK KENDARAAN BERMOTOR DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK MELALUI LAYANAN SAMSAT KELILING DI KOTA PANGKALPINANG - Septiani, Mutiara; Julia, Julia; Rudianto, Nur Ahmad Ricky (LPPM Universitas Bina Bangsa, 2025)
This study aims to analyze the influence of the tax collection system and tax knowledge on taxpayer compliance through mobile SAMSAT services in Pangkalpinang City. This study uses a quantitative approach using a survey method through a questionnaire distributed to 400 taxpayers. The results of this study indicate that mobile SAMSAT services and tax knowledge have a positive and significant effect on taxpayer compliance, while service quality does not have a significant effect on taxpayer compliance